The nature of political representation : voters’ perception towards the role of political representation - Rosyidah Muhamad; Ummu Atiyah Ahmad Zakuan; Nazli Aziz; Siti Aisyah Saat; Rohana Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2021)
There is a wide spectrum in academia that representatives of the citizens should act in line with the interests of those who are being represented. Knowledge about citizens’ preferences, however, is still limited in the field of political representation in Malaysia. This paper examines the MPs’ roles as the citizens’ representatives in Malaysia from the perspective of the citizens themselves. Based on the survey (n=598), the voters’ preferences that are being analysed through three models of representative-delegates, trustee and partisan. The research findings indicate that the constituents place a high priority on the MPs in bringing development to the constituency rather than in the law making and advocating. To this end, more expectations are for the MPs assemble to delegate model. Citizens perceive the MPs’ main role as a legislator as a minor role. This perception could reflect on the political situation in Malaysia. Accordingly, this paper suggests that the MPs should focus on their main functions in policy making, to participate in the parliamentary debates actively and to represent their constituencies at the national level. The MPs should take the local issues for national policies implementation to be contextualized in their respective local constituencies.